Employee Performance Effect In PT. "X" Company, Under The Impact of Servant Leadership Style and Motivation - Benyamin, Caesar; Prasetyo, Febi Panji; Widjana, Adang (Syntax Idea, 2021)
This research examines PT. "X" which engaged in automotive business sector, specifically in two-wheeled automotive under Honda brand. This study aims to determine the effect of servant leadership and work motivation on employee performance at PT "X". This research provides benefits as material and study or consideration as well as contribution from author for common readers, and particularly as an input for decision makers to improve employee performance at PT. "X". The method quantitative with the approach casusal explanatory by using a questionnaire as a data collection tool. The population of this research is 80 employees. The results shows that there is a positive influence between servant leadership and work motivation on performance.